2022
DOI: 10.3390/catal12090945
|View full text |Cite
|
Sign up to set email alerts
|

Production of Propanediols through In Situ Glycerol Hydrogenolysis via Aqueous Phase Reforming: A Review

Abstract: Production of 1,2-propanediol and 1,3-propanediol are identified as methods to reduce glycerol oversupply. Hence, glycerol hydrogenolysis is identified as a thermochemical conversion substitute; however, it requires an expensive, high-pressure pure hydrogen supply. Studies have been performed on other potential thermochemical conversion processes whereby aqueous phase reforming has been identified as an excellent substitute for the conversion process due to its low temperature requirement and high H2 yields, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 146 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…[17] Diols, such as 1,2-PD and propane-1,3-diol (1,3-PD), are useful products, largely employed in polymer industries (e. g., packaging, fiber, filler) that can be obtained by hydrogenolysis of GL. [18,19] The reaction is a variegated process that can be conducted, for example, on a metal-acid bifunctional catalyst, able to promote dehydration, via intermediates as hydroxyacetone (Hac) and 3-hydroxypropanal (3-HPA), followed by a hydrogenation reaction occurring on metal sites. [19] It was observed that increased aqueous GL conversion (from 53 % to 74 %) and 1,3-PD yield (from 20 % to 25 %) were obtained if TiO 2 was used as support for Pt/WO 3 -ZrO 2 catalyst, carrying out the reaction in a vertical stainless steel fixed-bed reactor at 523 K and 50 bar H 2 pressure.…”
Section: Titaniummentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Diols, such as 1,2-PD and propane-1,3-diol (1,3-PD), are useful products, largely employed in polymer industries (e. g., packaging, fiber, filler) that can be obtained by hydrogenolysis of GL. [18,19] The reaction is a variegated process that can be conducted, for example, on a metal-acid bifunctional catalyst, able to promote dehydration, via intermediates as hydroxyacetone (Hac) and 3-hydroxypropanal (3-HPA), followed by a hydrogenation reaction occurring on metal sites. [19] It was observed that increased aqueous GL conversion (from 53 % to 74 %) and 1,3-PD yield (from 20 % to 25 %) were obtained if TiO 2 was used as support for Pt/WO 3 -ZrO 2 catalyst, carrying out the reaction in a vertical stainless steel fixed-bed reactor at 523 K and 50 bar H 2 pressure.…”
Section: Titaniummentioning
confidence: 99%
“…[18,19] The reaction is a variegated process that can be conducted, for example, on a metal-acid bifunctional catalyst, able to promote dehydration, via intermediates as hydroxyacetone (Hac) and 3-hydroxypropanal (3-HPA), followed by a hydrogenation reaction occurring on metal sites. [19] It was observed that increased aqueous GL conversion (from 53 % to 74 %) and 1,3-PD yield (from 20 % to 25 %) were obtained if TiO 2 was used as support for Pt/WO 3 -ZrO 2 catalyst, carrying out the reaction in a vertical stainless steel fixed-bed reactor at 523 K and 50 bar H 2 pressure. [20] An explanation of this improvement could be the introduction of TiO 2 that increased the Brønsted acidity of the catalyst: WO x species were linked, through O bridges, to Zr but also to Ti, with a larger electronegativity than Zr.…”
Section: Titaniummentioning
confidence: 99%
“…Because it is non-toxic, it can also be used in the food industry, e.g., as a solvent for colourings and flavourings and as a sweetener [27]. In addition, it is also subjected to thermochemical conversion into polypropylene glycol [28] or acetol [29]. Purified glycerol also undergoes a number of chemical modifications, which make it a viable raw material for the production of dihydroxyacetone, epichlorohydrin, acrylic acid and glycerol esters and ethers [30].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, 1,3-propanediol (1,3-PD) is considered one of the most important valueadded chemicals which has been widely used in the polymer, pharmaceutical, and cosmetics industries. On an industrial scale, 1,3-PD is manufactured mainly from fossil-derived chemicals via Shell or Degussa processes [1][2][3]. However, the synthesis of 1,3-PD by bioconversion would be a step toward achieving sustainable development goals [4].…”
Section: Introductionmentioning
confidence: 99%